Anti-doping activites of volleyball in Japan. Issue 6 (10th April 2011) - Hashimoto, Y; Yamashita, T; Hamu, Y; Hayashi, M
Abstract : Background: Anti-doping activities are necessary for justice and fairness in sports. In and out of competition doping tests are now mainly responsible for anti-doping activities. Objective: To clarify the anti-doping activities in Japan in recent years. Design, setting, and participants: The object of the investigation is to summarize the doping tests performed after the volleyball games in Japan between 2006–2009. The anti-doping activities were mainly in the responsibility of the anti-doping subcommittee of the Japan Volleyball Association. This subcommittee is doing the coordination of drug testing in international games and domestic games. The competitions in which the doping tests were done were international games (Volleyball World Championship (VWC), World Cup (WC), World Grand Prix (WGP), Grand Champions Cup (GCC), and final preliminary qualifying contests (OQT) for the Olympic Games), and domestic games (V League, Emperor's Cup, and national constitution). Undergo doping test athletes were randomly chosen by lot from among all the participating players of the competition. Out-of-competition testing was based on the information ADAMS and whereabouts. All tests were urine, blood tests were not performed. All samples were carried to Mitsubishi Chemical Medience that was the only WADA official recognition analyzing facilities in Japan. Results: The number of samples increased every year, and the out of competition testing became a higher percentage of the total number of samples. The number of tests each year are as follows. Conclusions: There are many international games, and are many chances of the doping tests in Japan. Recently, the number of OOCT is increased. The most import ant thing is to raise awareness of anti-doping to individual players through the tests and the educational activities.